2004
DOI: 10.1088/0953-8984/16/48/019
|View full text |Cite
|
Sign up to set email alerts
|

Long-range chemical order effects upon the magnetic anisotropy of FePt alloys from anab initioelectronic structure theory

Abstract: The magnetocrystalline anisotropy (MCA) of bulk and thick films of FePt is calculated from a 'first-principles' theory. The starting point is a description from electronic density functional theory for systems of interacting electrons moving in lattices of ions. Relativistic effects such as spin-orbit coupling are included. FePt readily transforms into a CuAu-type (L1 0) ordered phase and this coincides with the material's high anisotropy. Here we describe how to calculate the MCA of a partially ordered alloy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
58
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 47 publications
11
58
0
Order By: Relevance
“…Daalderop et al [18] and Ravindran et al [12] studied the influence of the band-filling on E MCA of FePt. Many groups studied the influence of the temperature on the MCA of FePt [31,32]. The dependence of the Curie temperature on the FePt grain size was investigated via model Hamiltonian calculations [33].…”
Section: Introductionmentioning
confidence: 99%
“…Daalderop et al [18] and Ravindran et al [12] studied the influence of the band-filling on E MCA of FePt. Many groups studied the influence of the temperature on the MCA of FePt [31,32]. The dependence of the Curie temperature on the FePt grain size was investigated via model Hamiltonian calculations [33].…”
Section: Introductionmentioning
confidence: 99%
“…According to the modern first-principles theory of magnetic anisotropy [4][5][6], the magnetocrystalline anisotropy of L1 0 alloys is mainly related to the process of atomic ordering and depends on the degree of long order. It is experimentally shown that variation of temperature and duration of the ordering annealing and application of magnetic field or stresses in the course of this annealing, as well as of preliminary plastic deformation, are factors that exert a significant effect on the integral degree of long ordering, morphology and sizes of the meso-and microstructure elements of L1 0 alloys [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of theoretical and experimental works (e.g. [4][5][6][7][8][9][10][11][12][13][14][15]) the tetragonal distortion of the crystal lattice, which arises in the alloys upon the phase transformation A1 ! L1 0 , is considered to result exclusively from layer-by-layer distribution of atoms of different kinds in the directions h100i (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…3 The magnetic properties depend greatly on the degree of chemical order in the L1 0 phase. [4][5][6][7] However, FePt nanoparticles produced from room temperature sputtering and chemical synthesis process normally are in the disordered fcc phase and postsynthesis treatments are necessary to induce the phase transformation to the ordered L1 0 phase. Most postsynthesis treatments, such as thermal annealing, also lead to aggregation of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%